Interactive Diorama-Assisted Project-Based Learning to Improve Students IPAS Learning Motivation - Dianasari; Diana Setiana; Sri Rohana Fitriyah (Elementary Teacher Education Program, Majalengka University, 2026)
This study was conducted in response to the low learning motivation of elementary school students in Natural and Social Sciences, particularly in abstract ecosystem topics that are frequently taught through conventional instruction. The study aimed to examine the influence of Interactive Diorama-assisted Project-Based Learning on students’ learning motivation in Natural and Social Sciences. A quantitative approach with a quasi-experimental method and a nonequivalent control group design was employed. The participants were 46 fifth-grade students, consisting of 23 students in the experimental group and 23 students in the control group. The experimental group received Interactive Diorama-assisted Project-Based Learning, while the control group received conventional instruction. Data were collected using a 25-item learning motivation questionnaire administered before and after the treatment. Supporting data were obtained through a cognitive test, observation, and documentation. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, Independent Samples T-Test, and N-Gain Score. The findings revealed that the experimental group showed a greater improvement in learning motivation than the control group. The Independent Samples T-Test produced a significance value of 0.000, indicating a significant difference between the two groups. The experimental group obtained an N-Gain of 44.76% in the moderate category, while the control group obtained −12.21% in the low category. Thus, Interactive Diorama-assisted Project-Based Learning significantly improves elementary students’ learning motivation in Natural and Social Sciences and can serve as an active, visual, collaborative, and meaningful learning alternative.